Fiber optics-based surface enhanced Raman Spectroscopy sensors for rapid multiplex detection of foodborne pathogens in raw poultry - Mai Abuhelwa; Arshdeep Singh; Jiayu Liu; Mohammed Almalaysha; Anna V. Carlson; Kate E. Trout; Amit Morey; E. Kinzel; Lakshmikantha H. Channaiah; Mahmoud Almasri (Microsystems & Nanoengineering)
Abstract A new high-sensitivity, low-cost, Surface Enhanced Raman Spectroscopy (SERS) sensor allows for the rapid multiplex detection of foodborne pathogens in raw poultry. Self-assembled microspheres are used to pattern a hexagonal close-packed array of nanoantennas onto a side-polished multimode fiber core. Each microsphere focuses UV radiation to a photonic nanojet within a layer of photoresist on the fiber which allows the nanoantenna geometry to be controlled. Optimizing the geometry for the excitation layer generates electric field concentrations− referred to as a hotspot− within the analyte, thereby maximizing the Raman signal and improving the signal-to-noise ratio. The side polished configuration with a larger surface area has significantly better performance than the SERS sensor on the fiber tip. The use of additive manufacturing for the fiber polishing jigs as well as the sample testing compartment simplifies the sensor development and testing. Experimental results demonstrate a sensitivity range of 0.4–0.5 cells/ml achieved using raw chicken rinsates spiked with Salmonella typhimurium. Additionally, the sensor demonstrated its capability for multiplex and specific detection of Salmonella and E. coli O157:H7 with an optimal detection time of 10 min. The new sensor addresses a major global foodborne pathogen that poses significant public health concerns and can be readily adapted for the detection of other bacterial and viral pathogens such as E. coli O157:H7, Campylobacter, Listeria, and avian influenza and in other food products, e.g., dairy, beef, and produce, as well as clinical applications.